The Description Of Sea Cucumber On The Nearshore Soft-bottom Of Selected Sites In The Straits Of Malacca, Malaysia - Vincent, Teoh Yong Jian (2024)
Sea cucumbers are one of the targeted animals collected for food. As such, they possess commercial value and should be monitored. However studies on the description and diversity of sea cucumbers in the nearshore zones of the Straits of Malacca in Malaysia for the past ten years were limited to three studies. More studies are needed to manage sea cucumber stocks. This study was conducted to provide a description of the sea cucumbers on the nearshore soft-bottom zones of selected sites in the Straits of Malacca. Field samplings were conducted at Middle Bank, Tanjung Kupang, Blue Lagoon, and Merambong Shoal in the Straits of Malacca from April 2021 to June 2022 during low tide. Additional specimens from the collection of Centre for Marine and Coastal Studies (CEMACS) and USM were examined. Ossicles were extracted, examined, and photographed using a microscope with a camera attached. Images of ossicles were traced with ADOBE Photoshop. All specimens were preserved in CEMACS, USM. A total of 79 individuals were examined and 13 species of sea cucumbers were identified. Middle Bank had the highest diversity of sea cucumbers at eight species with a Diversity Index of 1.688 and Dominance Index of 4.405. Merambong Shoals had the second-highest diversity of sea cucumbers at five species with a Diversity Index of 1.423 and Dominance Index of 3.745. Two new species of sea cucumbers, Euthyonidiella zulfigaris sp. nov. and Acaudina spinifera sp. nov. were discovered and described.